SIZE EFFECT OF HYBRID LEARNING ON STUDENTS' SCIENCE LITERACY - Ni'mah Wahyuni; Achmad Ridlowi; Dharma Gyta Sari Harahap; Tomi Apra Santosa; Abdul Rahman (International Journal of Teaching and Learning, 2023)
This study aims to determine the effect size value of hybrid-based learning on science literacy students. This type of research is meta-analysis research. The data sources in this study came from 12 national and international journals published in 2018-2023. The search process data sources through Google Scholar, ERIC, and ScienceDirect databases. The word The keywords for the data search are "hybrid learning" and "student science literacy". Technique techniques were direct observation through journal databases and documentation. Analysis of data by calculating the effect size value of the entire research analyzed. analyzed. The results of this study conclude that the average effect size value of size (ES = 0.82) high criterion. This finding shows that hybrid learning has a significant effect on students' science literacy.